(untitled) (Modern education and development, 2025)
Transformer protection is a critical component of modern electrical power systems, ensuring operational safety and reliability. This paper explores the use of artificial intelligence (AI)-based relays in transformer protection systems. The study demonstrates how AI relays improve fault detection accuracy, reduce response time, and enhance the overall performance of power systems. Experimental results show significant improvements in protection efficiency compared to traditional relay systems.